2013
DOI: 10.3390/brainsci3020561
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase as a Therapeutic Target for Neuroprotection against Ischaemic Stroke: Future Perspectives

Abstract: Oxidative stress caused by an excess of reactive oxygen species (ROS) is known to contribute to stroke injury, particularly during reperfusion, and antioxidants targeting this process have resulted in improved outcomes experimentally. Unfortunately these improvements have not been successfully translated to the clinical setting. Targeting the source of oxidative stress may provide a superior therapeutic approach. The NADPH oxidases are a family of enzymes dedicated solely to ROS production and pre-clinical ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 226 publications
(389 reference statements)
0
28
0
2
Order By: Relevance
“…The cytosolic complex made up of p47, p67, and p40 phox proteins translocate to the membrane and dock with the membrane subunits in response to stimulation. [59] It is well known that gp91phox protein is the catalytic core of NADPH oxidase and mainly responsible for the formation of ROS in cells. [60] A previous study also showed the upregulation of gp91phox expression was associated with the increase in the activity of NADPH oxidase in response to LPS.…”
Section: Figurementioning
confidence: 99%
“…The cytosolic complex made up of p47, p67, and p40 phox proteins translocate to the membrane and dock with the membrane subunits in response to stimulation. [59] It is well known that gp91phox protein is the catalytic core of NADPH oxidase and mainly responsible for the formation of ROS in cells. [60] A previous study also showed the upregulation of gp91phox expression was associated with the increase in the activity of NADPH oxidase in response to LPS.…”
Section: Figurementioning
confidence: 99%
“…Pathogen‐killing respiratory/oxidative bursts by phagocytes are highly reliant on NADPH oxidase 2 (Nox2) whose activity, in turn, is subservient to pH changes. The optimal pH for Nox2 activity falls within ~7.2‐7.5 . Severe acidosis and rapid reverse in the circulating pH, as in highly alkali dialysate, would diminish Nox2 activity, compromising phagocytic capability of circulating and tissue phagocytes that are the principal components of innate immunity and the first line of defense against infection.…”
Section: Major Organ and Systemic Effects Of Acid‐base Alterationsmentioning
confidence: 99%
“…H 2 O 2 generated by the DUOX enzymes or by the dismutation of O 2 - can be scavenged by the antioxidants catalase (Cat) or glutathione peroxidase (GPx) and form H 2 O and O 2 , be partially reduced to generate hydroxyl radical (OH) by the Fe 3+ -catalyzed Haber-Weiss and Fenton reactions or react with chloride in a reaction catalyzed by myeloperoxidase, resulting in the formation of hypochlorous acid (HOCl; fig. 4) [121]. …”
Section: Ros/rns Generationmentioning
confidence: 99%